Pengaruh Konseling dengan Menggunakan Media Leaflet dalam Upaya Meningkatkan Pengetahuan dan Sikap Ibu tentang Cara Menyusui yang Benar di UPTD Puskesmas Tongauna Kabupaten Konawe - Rofiqoh, Rofiqoh; Martini, Martini (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2017)
Breastfeeding is still constrained by the lack of knowledge of mothers about the benefits of breastfeeding and the correct way of breastfeeding, the lack of lactation counseling services from health workers, the leave period is too short for working mothers, socio-cultural perceptions and the addition of formula milk, the aggressiveness of formula milk producers in promoting their products to consumers. community and health workers. To achieve successful breastfeeding, knowledge of correct breastfeeding techniques is required. This study aims to determine the effect of counseling using leaflets in an effort to increase knowledge and attitudes of mothers about the correct way of breastfeeding at the UPTD Puskesmas Tongauna. This research is a Quasi Experimental research. The population in this study were all pregnant women in the third trimester at the UPTD Puskesmas Tongauna, Konawe Regency totaling 60 people and a sample of 60 people (30 cases and 30 controls) taken by total sampling. Data was collected by means of interviews using questionnaires and data analysis to determine the effect of counseling on mothers' knowledge and attitudes about breastfeeding using the paired sample t-test. The study showed that 53.3% of the sample had poor knowledge before counseling, 66.7% of the sample had sufficient knowledge after counseling, 60% of the sample had a bad attitude before counseling and 63.3% of the sample had a good attitude after counseling. counseling. There was an effect of counseling on mother's knowledge and attitude about the correct way of breastfeeding (p=0.000).